1985
DOI: 10.1007/bf02388590
|View full text |Cite
|
Sign up to set email alerts
|

Defining ‘business ethics’: Like nailing jello to a wall

Abstract: ABSTRACT. Business ethics is a topic receiving much attention in the literature. However, the term 'business ethics' is not adequatdy defined. Typical definitions refer to the rightness or wrongness of behavior, but not everyone agrees on what is morally right or wrong, good or bad, ethical or unethical. To complicate the problem, nearly all available definitions exist at highly abstract levels. This article focuses on contemporary definitions of business ethics by business writers and professionals and on pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(145 citation statements)
references
References 10 publications
1
126
0
8
Order By: Relevance
“…Specifically, the definition of ethical business behaviour proposed by Lewis (1985) was used to define ethical practices as behaviours that indicate the use of "rules, standards, codes, or principles which provide guidelines for morally right behaviour and truthfulness in specific situations" (p. 381). In the present study, comments suggesting that participants demonstrated the application of ethical rules and principles within a commercial context and considered them important in running a business were categorised as "ethical practices".…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the definition of ethical business behaviour proposed by Lewis (1985) was used to define ethical practices as behaviours that indicate the use of "rules, standards, codes, or principles which provide guidelines for morally right behaviour and truthfulness in specific situations" (p. 381). In the present study, comments suggesting that participants demonstrated the application of ethical rules and principles within a commercial context and considered them important in running a business were categorised as "ethical practices".…”
Section: Resultsmentioning
confidence: 99%
“…In a broad sense, ethics is a set of moral principles and values that governs the behaviors of a person or group with respect to what is right or wrong. Ethics sets standards as to what is good or bad in conduct and decision making (Lewis, 1985, andCovey, S.R., 1991).…”
Section: What Is Managerial Ethics?mentioning
confidence: 99%
“…Ethics can be explained as the just or appropriate standards of behaviour by individuals in certain conditions (Runes, 1964;Trevin˜o et al, 2014;Sekerka et al, 2014). Synthesising different definitions, Lewis (1985) defines business ethics as comprising the rules, standards, principles or codes that give guidelines for morally right behaviour and truthfulness in a specific situation. Ethics is a philosophical term derived from the Greek word "ethos" meaning character or custom.…”
Section: Conceptual Frameworkmentioning
confidence: 99%